2012
DOI: 10.1007/s00894-012-1402-7
|View full text |Cite
|
Sign up to set email alerts
|

“Russian doll” complexes of [n]cycloparaphenylenes: a theoretical study

Abstract: The formation of "Russian doll" complexes consisting of [n]cycloparaphenylenes was predicted using quantum chemistry tools. The electronic structures of multiple inclusion complexes containing up to four macrocycles were explored at the M06-2X/6-31G* level of theory. The binding energy between the macrocycles increases from the center to the periphery of the complex and can be >60 kcal mol(-1) for macrocycles containing 14 and 19 repeating units. It has been demonstrated that additional electrostatic interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 28 publications
1
52
0
1
Order By: Relevance
“…Concerning the inclusion of molecules other than fullerenes into the [ n ]CPPs , a particularly promising class of guests are the CPPs themselves. In two theoretical studies, the groups of Fomine and Bachrach predicted that CPPs differing by five phenylene units would be shape‐complementary and form “Russian doll” complexes, in which two CPPs are aligned in a parallel manner . As shown in Figure a, Yamago and co‐workers demonstrated that these predictions are correct for a whole series of [ n ]CPPs ( n =5, 6, 7, 8, and 10) and that selective formation of complexes [ n +5]CPP ⊃ [ n ]CPP occurs, which represent the shortest possible analogues of double‐walled armchair carbon nanotubes .…”
Section: Host–guest Chemistrymentioning
confidence: 99%
“…Concerning the inclusion of molecules other than fullerenes into the [ n ]CPPs , a particularly promising class of guests are the CPPs themselves. In two theoretical studies, the groups of Fomine and Bachrach predicted that CPPs differing by five phenylene units would be shape‐complementary and form “Russian doll” complexes, in which two CPPs are aligned in a parallel manner . As shown in Figure a, Yamago and co‐workers demonstrated that these predictions are correct for a whole series of [ n ]CPPs ( n =5, 6, 7, 8, and 10) and that selective formation of complexes [ n +5]CPP ⊃ [ n ]CPP occurs, which represent the shortest possible analogues of double‐walled armchair carbon nanotubes .…”
Section: Host–guest Chemistrymentioning
confidence: 99%
“…A computational study by Fomine and co-workers examined the intriguing possibility of forming ''Russian doll'' supramolecular complexes of two, three or four differently sized CPPs. 55 Simple geometrical considerations suggested that an inclusion complex would ideally be formed between two CPPs differing in size by five phenylene units (it is stated this is a universal rule, regardless of specific ring size). Thus, the complexes to be studied were chosen to be combinations of [4], [9], [14] and [19]CPP.…”
mentioning
confidence: 99%
“…In each case, the ''hole'' is on the left, the ''particle'' on the right. Adapted with permission from ref 55…”
mentioning
confidence: 99%
“…[18] If aC PP also serves as ag uest for another CPP of different size, such ah ost-guest complex would be the shortest armchair double-walled CNT.I ndeed, Fomine predicted thatC PPs that differ by five phenylene units would have strong interactions with each other,a ss uch CPPs have differences in diameter close to 0.35 nm. [19] Indeed, Fomine also predicted, through DFT calculations at the M06-2X/6-31G(d) level of theory,t hat [4]-and [9]CPPs,a nd [9]-and [14]CPPs,w ould form "Russiandoll" complexes in which two CPPs are alignedi nap arallel manner.B achrach also reported that host-guest complexes are most stabilized when the host and guest differ by five phenylene units, as determined by DFT calculations at the wB97X-D/ 6-31G(d) level. [20] Bachracha lso showed that this functional gives better results than M06-2X, andt hat these complexes adopt a" planetary orbit" structure, inw hich two CPPs are inclined with respect to each other,i nsteado ft he Russian-doll configuration.…”
mentioning
confidence: 99%